Association between Leadership, Motivation, Compensation and Employees Satisfaction in Primary Health Centres Denpasar - Made Karma Maha Wirajaya; Ni Made Sri Nopiyani; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Employees satisfaction can improve the work performance of employees that can create a positive situation in the organizational environment. Previous studies have shown that leadership, motivation and compensation related to employee satisfaction but has not been able to explain the association of leadership, motivation and compensation together with employee satisfaction. This study aims to determine the relationship of leadership, motivation, compensation and employees satisfaction in primary health centers, Denpasar. Methods: This study was cross-sectional survey among all employees consist of 39 employees in Puskesmas II Denpasar Selatan and 36 employees in Puskesmas III Denpasar Utara. Data were collected using a questionnaire and analyzed using logistic regression to examine the association between leadership, motivation, compensation and employees satisfaction in primary health centers, Denpasar. Results: Most employees perceived lack in leadership of the head of primary health centers (52.00%), had a high motivation to work (56.00%), received adequate compensation (60.00%) and satisfied with their work (52.00%). Multivariate analysis showed that two variables had significant association, that were leadership with OR=7.28 (95%CI:=2.17-24.46) and motivation with OR=4.31 (95%CI: 1.29-14.39). Conclusion: Factors associated to the employees satisfaction in primary health centers were leadership and motivation. Aspects of leader behavior to motivate employees and extrinsic motivation primarily on working conditions need to be improved to create employees satisfaction.